Geometry of anchoring miniscrew in the lateral palate that support a tissue bone borne maxillary expander affects neighboring root damage - Song Hee Oh (Nature Portfolio, 2021)
Abstract Anchoring miniscrews used for a tissue bone borne maxillary expander (C-expander) can fail if they contact tooth roots or perforate the maxillary sinus. Cone beam computed tomography images were reviewed retrospectively to evaluate the geometric factors of miniscrew placement in the palate that contribute to root proximity (RP) and sinus perforation (SP), and to investigate the differences of miniscrew placement depth (PD) and placement angle (PA) among the groups in each variable from 340 anchoring miniscrews on 70 patients whose C-expanders showed sufficient stability after palatal expansion for orthodontic treatment. Two types of miniscrews were used: a self-tapping miniscrew with 1.8 mm-in-diameter, and a self-drilling miniscrew with 1.6 mm-in-diameter. While the self-tapping larger diameter miniscrew influenced root proximity significantly, the screw location and PD affected the rate of sinus perforation. PA was significantly different between the right and left sides of the palate. The results of this study confirmed that root proximity and sinus perforation of anchoring miniscrews in a tissue bone borne palatal expander occurred due to certain risk factors, even when the palates were expanded successfully. Knowledge of these factors can help the clinician place miniscrews with less risk of root proximity or sinus perforation.